Pengaruh Persepsi Kemudahan, Persepsi Manfaat, Dan Kepercayaan Terhadap Minat Menggunakan Go-Pay - Cindriyani; Fathihani (CV ODIS, 2023)
This research is a quantitative study that aims to determine the effect of perceived convenience, perceived benefits and trust on interest in using Go-Pay. The population in this study were Dian Nusantara University students, especially Go-Pay users. The samples taken in this study amounted to 100 using a purposive sampling method. Data collection was carried out by distributing questionnaires via the Google form, and data processing using SmartPLS. The results of the test showed that the perceived ease of use variable did not have a positive and significant effect on the intention to use by 0.364, the perceived benefit variable did not have a positive and significant effect on the intention to use by 0.676, the trust variable had a positive and significant effect on the intention to use by 5.979